2015
DOI: 10.1007/s10554-015-0746-3
|View full text |Cite
|
Sign up to set email alerts
|

Subtraction coronary computed tomography in patients with severe calcification

Abstract: To investigate the clinical usefulness of subtraction coronary computed tomographic angiography (CCTA) in patients with severe calcification. A 320-row area detector CT system was used in this study. The subjects were 78 patients (47 men and 31 women, 739 years of age) with an Agatston score of >300 who were able to undergo prospective one-beat scanning during a single breath-hold. The CCTA findings were compared against invasive coronary angiography. The diagnostic capabilities of CCTA for the severely calcif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 23 publications
1
24
1
2
Order By: Relevance
“…In subtraction CCTA, to minimize misregistration artefact due to differences in the breath-hold position, the two scans for obtaining the mask image (mask scan) and post-contrast image (post-contrast scan) should ideally be performed in a single breath-holding. 3 A previous study using test injection method reported that breath-holding time is in the range of 20-40 s. 5 Another study using test injection method reported by Kidoh et al 14 demonstrated that they could shorten the breathholding time to approximately 20 s. On the other hand, Amanuma et al 6,7 reported that the breath-holding time was approximately 25 s using bolus-tracking method. They also described that subtraction CCTA could not be performed in some patients despite the administration of supplemental oxygen.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In subtraction CCTA, to minimize misregistration artefact due to differences in the breath-hold position, the two scans for obtaining the mask image (mask scan) and post-contrast image (post-contrast scan) should ideally be performed in a single breath-holding. 3 A previous study using test injection method reported that breath-holding time is in the range of 20-40 s. 5 Another study using test injection method reported by Kidoh et al 14 demonstrated that they could shorten the breathholding time to approximately 20 s. On the other hand, Amanuma et al 6,7 reported that the breath-holding time was approximately 25 s using bolus-tracking method. They also described that subtraction CCTA could not be performed in some patients despite the administration of supplemental oxygen.…”
Section: Discussionmentioning
confidence: 98%
“…They also described that subtraction CCTA could not be performed in some patients despite the administration of supplemental oxygen. 6 Recently, modified subtraction CCTA with a short breathholding time using bolus-tracking method was reported. Although this investigation confirmed that this method could shorten the breath-holding time to ,15 s while providing diagnostic images, the diagnostic accuracy of the evaluation of significant stenosis itself was not evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This effective method allows calcium to be subtracted from coronary computed tomography angiography (CCTA) images, providing improved diagnostic accuracy over conventional CCTA in patients with severe coronary artery calcification and stent (1)(2)(3)(4)(5)(6)(7). SCCTA uses two CCTA datasets collected pre-contrast and after contrast enhancement.…”
Section: Introductionmentioning
confidence: 99%